Lethal Mutagenesis of Hepatitis C Virus Induced by Favipiravir - de Ávila, Ana I. (PLoS One, 2016)
Lethal mutagenesis is an antiviral approach that consists in extinguishing a virus by an excess of mutations acquired during replication in the presence of a mutagen. Here we show that favipiravir (T-705) is a potent mutagenic agent for hepatitis C virus (HCV) during its replication in human hepatoma cells. T-705 leads to an excess of G → A and C → U transitions in the mutant spectrum of preextinction HCV populations. Infectivity decreased significantly in the presence of concentrations of T-705 which are 2- to 8-fold lower than its cytotoxic concentration 50 (CC(50)). Passaging the virus five times in the presence of 400 μM T-705 resulted in virus extinction. Since T-705 has undergone advanced clinical trials for approval for human use, the results open a new approach based on lethal mutagenesis to treat hepatitis C virus infections. If proven effective for HCV in vivo, this new anti-HCV agent may be useful in patient groups that fail current therapeutic regimens.